Роль технологій штучного інтелекту в поширенні та боротьбі з дезінформацією - Лучко, Юлія Іванівна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The development of artificial intelligence has an inherent impact on modern society, but it introduces new challenges, particularly in the field of disinformation. Its capabilities, such as content generation and deepfake technology, become tools for information manipulation. The analysis shows the use of AI by special services, which leads to the spread of fake news and the creation of false images. However, intelligent systems can also be effective in detecting misinformation through pattern recognition. For example, Ukrainian services use analytical algorithms and systems to counter information threats, taking into account the importance of the balance between innovation and security.